Application of calcium phosphate as remineralizing agent in oral healthcare: a bibliometric and scientometric analysis / Amin Saiff Johari [et al.] - Johari, Amin Saiff; Zulkepli, Nur Ayunie; Tarmizi, Nur Hazirah; Mokhtar, Norehan; Sarmoko, . (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
There has been increased interest in developing bioactive agents based on calcium phosphate (CaP) in oral care for enhancing enamel and dentin remineralization. This bibliometric and scientometric analysis explores the interdisciplinary view of calcium phosphates-based for alternative oral care concepts in preventive dentistry. Bibliometric analyses were performed using VOSviewer software taking SCOPUS as the main database for literatures retrieval. The analysis revealed highest number of CaP-related articles were published within 10 years that provide insights into the past and recent trends in the applications of CaP in oral care. Further, top three countries with the highest number of publications includes, the United States (n=58), China (n=50) and India (n=23). Finally, present study provides data on literatures, countries and authors that have been involved in CaP research extensively for the past years. Also, this study will help researchers, academicians and students to find suitable article for their referral in terms of the use of CaP as a biomaterial in dentistry.